Guided discovery of chemical reaction pathways with imposed activation. Issue 46 (15th November 2022) - Lavigne, Cyrille; Gomes, Gabe; Pollice, Robert; Aspuru-Guzik, Alán
Abstract : Activation of a single user-selected coordinate such as stretching of a bond combined with a constrained conformer search via metadynamics allows chemical reaction pathways and the associated transition structures to be explored comprehensively. Abstract : Computational power and quantum chemical methods have improved immensely since computers were first applied to the study of reactivity, but the de novo prediction of chemical reactions has remained challenging. We show that complex reaction pathways can be efficiently predicted in a guided manner using chemical activation imposed by geometrical constraints of specific reactive modes, which we term imposed activation (IACTA). Our approach is demonstrated on realistic and challenging chemistry, such as a triple cyclization cascade involved in the total synthesis of a natural product, a water-mediated Michael addition, and several oxidative addition reactions of complex drug-like molecules. Notably and in contrast with traditional hand-guided computational chemistry calculations, our method requires minimal human involvement and no prior knowledge of the products or the associated mechanisms. We believe that IACTA will be a transformational tool to screen for chemical reactivity and to study both by-product formation and decomposition pathways in a guided way.